Two Electro-weak Phases in the \(SU(2)_1 \otimes SU(2)_2 \otimes U(1)_Y\) Model - Phong, Vo Quoc; Anh, Nguyen Minh (Communications in Physics, 2019)
Our analysis shows that SM-like electroweak phase transition (EWPT) in the \(SU(2)_1 \otimes SU(2)_2 \otimes U(1)_Y\) (2-2-1) model is a first-order phase transition at the $200$ GeV scale, enough for baryogenesis. This first order EWPT is described by a non-smooth correlation length function. The second VEV is larger than 1.1 TeV in a two-stage EWPT senarino